Discrimination of Female Characters Due to Patriarchal Power in the Novel Entrok by Okky Mandasari - Nenabu, Febryanti Marsalin; Suroso (PT FORMOSA CENDEKIA GLOBAL, 2024)
In society, discrimination against female figures often occurs, especially because patriarchal power continues to reign. A social system that gives greater benefits and control to men is called patriarchal power. In contrast, women often face restrictions, stereotypes and unfair treatment. The purpose of this service is to gain an understanding of the effects and consequences of discrimination against female figures resulting from patriarchal power and to make a contribution to society. It is hoped that this research will discover various types of discrimination experienced by female characters, and how this discrimination impacts their lives and society as a whole. This research uses the content analysis method. In the novel Entrok by Okky Mandasari, there are still many acts of discrimination against women due to patriarchal power